INPATIENT SATISFACTION ANALYSIS OF THE NATIONAL HEALTH INSURANCE USERS IN QUALITY SERVICES IN WARD OBSTETRICS AND GYNECOLOGY HOSPITAL YOGYAKARTA SLEMAN - Shanendra Ulfa F; Abdul Karim Zulkarnain (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Along with the expanding world of health, the hospital’s role has grown into a service industry that is strongly influenced by the market. Consumers have become one factor in determining the existence of the service industry. Customer satisfaction becomes an important thing that needs to be considered in order to sustain the industry from fierce competition. The purpose of this study was to measure the level of satisfaction of the patients on the National Health Insurance in obstetrics and gynecology hospital ward Yogyakarta Sleman, especially in terms of quality of service. Samples are selected patients with accidental sampling method with a number of 100 respondents. Research instrument used was a questionnaire with closed questions. Data were processed descriptively and analyzed to determine the level of compatibility between performance and expectations along with paired t test, gap test, chi square test and contingency coefficient. Based on Cartesian diagram the service performance of assurance, empathy, and tangibles dimensions have been implemented well and its performance should be maintained. While the dimensions of reliability and responsiveness is considered less important for the patient. Patients are not satisfied on the dimensions of reliability, responsiveness, assurance, and empathy. While the patients had been satisfied in tangibles dimension, characteristics of age and education did not significantly influence patient satisfaction. Whereas, the employment and income characteristics significantly influence patient satisfaction.